The Effect of Knowledge Sharing and Enrichment on Lecturer Innovation Performance in General Achmad Yani University - Pudjiantoro, Tacbir Hendro; Anggoro, Sigit; Destiani, Dea (Universitas Bina Sarana Informatika, 2024)
The annual evaluation carried out by LLDIKTI looked at the performance of lecturers in their regions, and it was revealed that some lecturers, especially lecturers at Jenderal Ahmad Yani University (UNJANI), still had difficulty fulfilling the tridharma duties of teaching, research and community service, which are important aspects of higher education. To consistently fulfill these obligations, lecturers are required to innovate. A study aimed at exploring how knowledge exchange and enrichment impact the innovative performance of UNJANI lecturers, collecting data through an online survey distributed to them. This research aims to understand the influence of knowledge sharing and enrichment on lecturer innovation, and its success is assessed through questionnaire analysis. These findings underscore the important positive correlation between knowledge sharing, enrichment, and increased innovative performance among UNJANI lecturers, indicating that encouraging these practices can increase the fulfillment of tri dharma obligations.